Vaccine hesitancy with a history of Guillain Barre Syndrome: Weighing the risks and benefits of SARS-CoV-2 vaccination. (2022) - Murawska Baptista, Aleksandra; Alok, Akankcha; Libertin, Claudia
Abstract: Since the beginning of the COVID-19 pandemic, great hesitancies regarding the COVID-19 immunization have existed. The most striking adverse events reported include thrombosis with thrombocytopenia syndrome (TTS), myocarditis, and Guillain Barre Syndrome (GBS). Post-vaccination GBS is known since the time of Influenza vaccination, but several cases of GBS have also been reported in the current COVID-19 vaccination era. As a result, our patient with a history of GBS post-Influenza vaccination, went unvaccinated for SARS-CoV-2, due to fear of GBS re-activation. Consequently, he contracted COVID-19 pneumonitis complicated with deep venous thrombosis, requiring a prolonged hospitalization. Weighing the risks and benefits of vaccination to COVID-19 is difficult, especially for people with a previous history of GBS related to Influenza vaccination. We reviewed and analyzed the reported cases of GBS temporary related to COVID-19 vaccination to determine the safety of their administration in those with a history of GBS.